Evaluating Face and Content Validity of Digital Literacy, Technology Acceptance, and Behavioural Intention Questionnaire for TVET - Zainuddin, Kamilah; Mat Daud, Khairul Azhar; Mahmud, Yus Heary (Journal of Human Capital Development (JHCD), 2025)
The COVID-19 pandemic has had far-reaching repercussions on education systems, career pathways, and employment opportunities, with significant implications for individuals, communities, and national economies. In this context, graduate employability has emerged as a critical concern. Malaysia’s distinctive socio-economic landscape provides a compelling setting for examining the challenges and opportunities faced by graduates seeking stable and meaningful employment in the post-pandemic period. This study adopts a thematic analysis approach to explore the employability experiences of recent Malaysian graduates. Insights are derived from a focused review of relevant literature and survey data capturing graduates’ employment dynamics during and after the COVID-19 pandemic. Furthermore, the study empirically validates the key employability themes conceptualized through survey responses to enhance the robustness of the findings. The results indicate that Malaysian graduates face substantial employability challenges in the post-COVID-19 labour market, driven by changing employment structures and evolving skill requirements. The findings highlight the critical role of innovative career exploration, adaptability, and graduates’ self-awareness of labour market trends in improving employability outcomes. The study underscores the need for context-specific employability strategies tailored to Malaysia’s socio-economic conditions. These findings offer valuable implications for policymakers, higher education institutions, and graduates in designing targeted interventions to enhance employability in an increasingly dynamic post-pandemic labour market.